Enhancing green loyalty in 3-star hotels in Surabaya: The role of green image, green marketing, and the mediation of green satisfaction and green trust - Mahendra, I.G.N. Andhika; Ujianto, Ujianto; Halik, Abdul (Edelweiss Applied Science and Technology, 2025)
The increasing awareness of environmental issues has led to the adoption of eco-friendly products and services, prompting hotels to implement the Green Hotel concept. This research explores the impact of Green Marketing and its relationship with Green Satisfaction, Green Trust, and Green Loyalty among 3-star hotel customers in Surabaya. The study uses Green Marketing Mix theory and examines how Green Image, Green Product, Green Price, Green Place, and Green Promotion affect Green Satisfaction and Green Trust. Additionally, it investigates the influence of Green Satisfaction and Green Trust on Green Loyalty. The research employs a causal explanatory approach with purposive sampling, targeting customers over 20 years old. Data analysis uses Structural Equation Modeling (SEM) with SmartPLS software. Findings show that Green Image, Green Product, Green Price, and Green Promotion positively affect Green Satisfaction and Trust, but Green Place does not significantly influence Green Trust. Green Satisfaction and Trust both positively affect Green Loyalty.